The Role of Synthetic Organic Electrochemistry in the Technological Revolution of Pharmaceutical Industry - Gabriele Laudadio (CHIMIA, 2025)
Electrochemistry is significantly contributing to the technological revolution of organic synthesis, where the implementation of different techniques has garnered innovative and scalable synthetic methodologies. This article explores the impact of synthetic organic electrochemistry in the pharmaceutical and agrochemical industry. Key examples in high throughput experimentation, medicinal chemistry, discovery process chemistry, and process chemistry are presented, highlighting the relevance of electrochemistry in the advancement of organic synthesis, and driving innovation in the fine chemical industry.